Academic Supervision in the Improvement of Teachers' Professional Competencies: Effective Practices on the Emergence - Lorensius Lorensius; Nikolaus Anggal; Stepanus Lugan (EduLine: Journal of Education and Learning Innovation, 2022)
This study aims to identify and analyze the implementation of academic supervision in improving the professional competence of teachers. The method used is a qualitative approach with a case study design. Collecting data using observation and interview techniques, then interview data were analyzed using manifest analysis. The results show that academic supervision carried out by school principals can help, guide, and motivate teachers in improving their professional abilities, especially in the process of teaching and learning activities in the classroom. Through a systematic and well-planned supervision process, teachers are able to fully integrate and apply their various abilities in learning through input from peers. In addition, teachers can take lessons from reflection exercises which are a hallmark of teacher professionalism. Supervisors and teachers can also know and understand the importance of academic supervision for improving the professional competence of teachers and ultimately having an impact on improving student learning outcomes.